Cynomolgus monkey testicular cDNAs for discovery of novel human genes in the human genome sequence - Osada, Naoki (BioMed Central, 2002)
BACKGROUND: In order to contribute to the establishment of a complete map of transcribed regions of the human genome, we constructed a testicular cDNA library for the cynomolgus monkey, and attempted to find novel transcripts for identification of their human homologues. RESULT: The full-insert sequences of 512 cDNA clones were determined. Ultimately we found 302 non-redundant cDNAs carrying open reading frames of 300 bp-length or longer. Among them, 89 cDNAs were found not to be annotated previously in the Ensembl human database. After searching against the Ensembl mouse database, we also found 69 putative coding sequences have no homologous cDNAs in the annotated human and mouse genome sequences in Ensembl. We subsequently designed a DNA microarray including 396 non-redundant cDNAs (with and without open reading frames) to examine the expression of the full-sequenced genes. With the testicular probe and a mixture of probes of 10 other tissues, 316 of 332 effective spots showed intense hybridized signals and 75 cDNAs were shown to be expressed very highly in the cynomolgus monkey testis, but not ubiquitously. CONCLUSIONS: In this report, we determined 302 full-insert sequences of cynomolgus monkey cDNAs with enough length of open reading frames to discover novel transcripts as human homologues. Among 302 cDNA sequences, human homologues of 89 cDNAs have not been predicted in the annotated human genome sequence in the Ensembl. Additionally, we identified 75 dominantly expressed genes in testis among the full-sequenced clones by using a DNA microarray. Our cDNA clones and analytical results will be valuable resources for future functional genomic studies.